Portable rotating grating stimulation for anisometropic amblyopia with 6 months training - Wen-Hsiu Yeh; Li-Ju Lai; Da-Wei Chang; Wei-Sin Lin; Guan-Ming Lin; Fu-Zen Shaw (Scientific Reports, 2021)
Abstract Treatment of grating stimulation has been used in amblyopia for decades, but high dropout rate and inconvenience for daily practice occur in previous studies. We developed a home-based portable system with rotating grating stimulation on a tablet. Thirty anisometropic amblyopic children were randomly allocated into the control or Grating group. They drew contour of the picture under patch of a better eye for 6 months. Best-corrected visual acuity (BCVA), grating acuity (GA), and contrast sensitivity (CS) were assessed at the baseline, 1st, 2nd, 3rd, and 6th months of training. All participants completed the 6-month training. Patched eyes of both groups exhibited no difference. Trained eyes of the control group had significantly slight improvement in BCVA and GA. In particular, the Grating group exhibited significantly higher BCVA, GA, and CS compared with those of the control group at the 3rd and 6th months of training. Moreover, percentage of the Grating group with great improvement (BCVA ≥ 0.3 or CS ≥ 0.3) was significantly larger than those of the control group at the 3rd or 6th months of training. The portable grating stimulation system demonstrates its trainability by no dropout and effectiveness by significant improvements in all assessments through a well experimental design. Trial Registration: ClinicalTrials.gov NCT04213066, registered 30/12/2019, https://clinicaltrials.gov/ct2/show/NCT04213066 .